PENGARUH SIKAP MENGAJAR GURU TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PJOK - prasetiyo, rahayu; susanto, nugroho (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2021)
The purpose of this study was to determine the analysis of teachers' teaching attitudes towards students' learning motivation and also to find out which teaching attitudes motivated students the most. This research is a quantitative research with Ex Post Facto method. Subjects in this study amounted to 274 students. Collecting data in this study in the form of a questionnaire. Based on the results of calculations from One Way Anova through the SPSS program, there are significant differences in the three teachers' teaching attitudes in influencing students' learning motivation with a significant value of 0.000 which is smaller than the significant level of 0.05. Real teaching attitudes with permissive teaching attitudes have a significant difference in influencing students' learning motivation, as evidenced by a significant value of 0.000 <0.05. Authoritarian teaching attitude with permissive teaching attitude has a significant difference in influencing student learning motivation, as evidenced by a significant value of 0.000 <0.05. However, there is no significant difference between real teaching attitudes and authoritarian teaching attitudes in influencing learning motivation, as evidenced by a significant value of 0.126 > 0.05. Meanwhile, the teaching attitude of the teacher which has the greatest influence on students' learning motivation is the real teaching attitude with a value of 4.896. In the second place, there is an authoritarian teaching attitude that has an influence on students' learning motivation with a value of 3,624. And lastly, there is a permissive teaching attitude which has an influence on learning motivation with a value of -3.624.